REV7 is required for anaphase-promoting complex-dependent ubiquitination and degradation of translesion DNA polymerase REV1 - Chun, Abel Chiu-Shun (Landes Bioscience, 2013)
REV1 is a Y-family polymerase specialized for replicating across DNA lesions at the stalled replication folk. Due to the high error rate of REV1-dependent translesion DNA synthesis (TLS), tight regulation of REV1 activity is essential. Here, we show that human REV1 undergoes proteosomal degradation mediated by the E3 ubiquitin ligase known as anaphase-promoting complex (APC). REV1 associates with APC. Overexpression of APC coactivator CDH1 or CDC20 promotes polyubiquitination and proteosomal degradation of REV1. Surprisingly, polyubiquitination of REV1 also requires REV7, a TLS accessory protein that interacts with REV1 and other TLS polymerases. The N-terminal region of REV1 contains both the APC degron and an additional REV7-binding domain. Depletion of REV7 by RNA interference stabilizes REV1 by preventing polyubiquitination, whereas overexpression of REV7 augments REV1 degradation. Taken together, our findings suggest a role of REV7 in governing REV1 stability and interplay between TLS and APC-dependent proteolysis.